Surgical approach for complete resection of giant retroperitoneal liposarcoma with diaphragmatic hernia via ninth rib thoracotomy - Hu, Bai-e; Wu, Chang-lei; Liu, Ji-peng; Zhang, Wen-jun (Frontiers in Oncology, 2023)
Background: Resection of a giant retroperitoneal liposarcoma is difficult and technically demanding, especially for large retroperitoneal tumors accompanied by a diaphragmatic hernia. Technically, the open abdominal approach can be timeconsuming and difficult to perform, with possible intraoperative complications and other factors bringing psychological and physical difficulties to the patient. This study reports a safe and feasible approach for the complete resection of a large retroperitoneal tumor complicated by a diaphragmatic hernia.A 58-year-old male patient with persistent upper abdominal pain and distension was treated at a local hospital on July 4, 2022. Computed tomography showed a mixed-density mass on the right retroperitoneum, and liposarcoma was considered. On July 6, 2022, the patient was transferred to our hospital for further treatment. Computed tomography showed a mass with fatty low-density shadow in the right adrenal region. The boundary with the right adrenal gland was unclear. The mass was 102 × 74 mm, and the right lobe of the liver was compressed. Insufficiency of the right middle lobe of the liver was seen due to a right diaphragmatic hernia and left mediastinal deviation. We considered the traditional approach for tumor resection via laparotomy, but we opted to perform a comprehensive evaluation first. The tumor was close to the back of the right kidney and liver, causing the diaphragm to rise because of its proximity to these organs. Exposing the tumor through laparotomy would be difficult, making it challenging to remove. The patient had a diaphragmatic hernia and moderate pulmonary dysfunction; therefore, we decided to enter the abdomen through a thoracotomy of the ninth rib.Results: Using our technique, the tumor was easily visualized and completely removed in approximately 30 minutes. The intraoperative blood loss was 100 ml, and no postoperative bleeding, pneumothorax, intestinal fistula, infection, or other complications occurred.The transthoracic approach may be a safer and more feasible resection method than the traditional open approach for patients with giant retroperitoneal liposarcoma with diaphragmatic hernia.